Oral gingival myiasis: A rare case report and literature review - Dheeraj Sharma; Sandeep Kumar; Pranav Parashar; Vihang Vinod Naphade (Wolters Kluwer Medknow Publications, 2015)
Myiasis is a universal term for extreme infection by the parasitic fly larvae that feed on their host living/dead tissue. Gingival myiasis is a rare disease in the humans associated with poor oral hygiene, suppurative oral lesions, alcoholism, and senility, among other conditions. We present a case of gingival myiasis in the maxillary anterior region on the palatal surface in a 21-year-old mentally challenged male with moderate periodontitis and neurologic deficit. The diagnosis was made on the presence of larvae in the lesion. Treatment done was a manual removal of the larvae, one by one, with the help of the clinical forceps, surgical debridement of the oral wound, and subsequent management of the periodontal disease.